In Vivo and Simulation Study of Artificial Ventilation Effects on Energetic Variables in Cardiosurgical Patients - De Lazzari, C.; Darowski, M.; Wolski, P.; Ferrari, G.; Tosti, G.; Pisanelli, D. M. (Methods of Information in Medicine, 2005)
Objectives: The analysis of energetic ventricular variable changes during artificial ventilation, obtained by numerical simulation was done. Twenty-one sets of hemodynamic parameters for eight cardiosurgical patients were used to estimate left and right stroke work. The data were collected for three methods of ventilation: conventional, lung-protective (with minute ventilation diminished by half) and high frequency ventilation (with frequency 5, 10, or 15 Hz).Methods: The computer simulator (CARDIOSIM©) of the cardiovascular system, was used as a tool to calculate values of energetic ventricular variables for conditions that corresponded to these during in vivo measurements. Different methods of ventilation caused differences of intrathoracic pressure, haemodynamic and finally energetic ventricular variables. The trends of these variable changes were the same in in vivo and simulation studies, in the whole range of intrathoracic pressure changes (Pt = 1.5-3.5 mmHg).Results: As values of main hemodynamic variables like cardiac output or arterial, systemic and pulmonary pressures were very close in both studies. Cardiac index and left ventricular stroke work also differed less than 10% for all examined patients and computer simulation. In a case of right ventricular stroke work the difference between in vivo data and simulation was a bit greater than 10% for two of eight patients under study.Conclusions: Our comparative analysis proved that numerical simulation is a very useful tool to predict changes of main hemodynamic and energy-related ventricular variables caused by different levels of positive Pt. It means that it can help an anesthesiologist to choose an appropriate method of artificial ventilation for cardiosurgical patients.
Keywords: Mock circulatory system; mechanical ventilation; computer simulation; energetic variables; haemodynamics; intrathoracic pressure